2005
DOI: 10.1136/aim.23.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Laser Acupuncture for the Treatment of Neurogenic Pruritus in a Child – a Case History

Abstract: This report describes the successful treatment using laser acupuncture of a six year old girl with neurogenic pruritus of the abdomen. It is the first case report of neurogenic pruritus treated by laser acupuncture. The main advantage of using low energy laser, as opposed to acupuncture needles, to stimulate points, is that low energy laser causes little or no sensation, which is particularly useful when treating children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…It is also unknown whether repeated needle stimulation may alter sensory processing and responses to subsequent painful stimuli, in the same manner like heel sticks, necessary to take blood samples [6, 39, 57]. LA is a painless procedure, and therefore, it becomes a more and more relevant alternative to manual acupuncture in infants [714]. But the central and peripheral effects and the applied doses in neonates and infants undergoing laser acupuncture are a matter of fact in ongoing discussions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also unknown whether repeated needle stimulation may alter sensory processing and responses to subsequent painful stimuli, in the same manner like heel sticks, necessary to take blood samples [6, 39, 57]. LA is a painless procedure, and therefore, it becomes a more and more relevant alternative to manual acupuncture in infants [714]. But the central and peripheral effects and the applied doses in neonates and infants undergoing laser acupuncture are a matter of fact in ongoing discussions.…”
Section: Resultsmentioning
confidence: 99%
“…However it is unknown whether repeated needle stimulation may alter sensory processing and responses to subsequent painful stimuli [6] or demonstrates an increased infection risk in premature babies [7]. LA application is painless and can avoid infections, which could be an important alternative to manual acupuncture in infants [814]. However, the applied doses, duration of stimulation, peripheral, and central effects of LA are an ongoing discussion [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have demonstrated the efficacy of acupuncture on itch in humans [12, 36–38]. Investigations by Han et al [25] explored the anti-pruritic effects of acupuncture in a rat model of hindlimb scratching.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, low-intensity laser stimulation of acupoints is known not to activate the peripheral nerve at the acupoint. 39,40 CONCLUSIONS Studies of the human meridian system have made much progress, and a few hypotheses that attempt to explain the wide range of physiological effects of acupuncture in humans have been suggested such as the bioelectricity theory, neural opiate theory, neural non-opiate theory, and hormonal opiate theory. 1 However, no one mechanism can explain all the physiological effects that are observed.…”
Section: Blood Flow Effect Of Acupuncturementioning
confidence: 99%